(3GdeNJGQ aj eSCdI GdcMds - (3eMeO Hf SdjeGf Hf SYO Hf eSYhO GdcGajLj GdQhej GdMfaj, eMjj GdOjf, CHh YHO Gddg, J (B879 (3g` s
(3ChdgG (B:s
(3hHYO, agPG fHP jSjQ hLjR GdfXe hajg ebOeI hKdGKI eWGdH hNGJeI hJPfjH s
(3BNQgG (B:s
(3adhdG GdNha ef SBeI GdNhGWQ HGdCWfGH dChQOfG ggfG JMbjbGJ adfcJa HgPG GdbOQ GdjSjQ ef GdNWGH hdfSeg fRgI GdCUMGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3ajg VHWs
(3hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B150s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B282 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs